Mangrove Forest Ecotourism Program Development Tongke-tongke in Sinjai Regency - Rifdan Rifdan; Indra; Sitti Hardiyanti Arhas; Suprianto Suprianto (Jurnal Penelitian Pendidikan IPA, 2023)
The growth of tourism as an industry has recently shown a very increasing graph and has even been able to boost Indonesia's economic growth for the better. The development of mangrove ecotourism is an effort to utilize environmental services from coastal areas in a sustainable manner. This research is to find out the potential and problems as well as a SWOT analysis of ecotourism in the Tongke-tongke Mangrove Forest in Sinjai Regency so that a better and more sustainable ecotourism program can be developed. The findings show that there are potentials and problems in Mangrove Forest ecotourism in terms of public facilities, biological aspects, recreational aspects, educational aspects, conservation aspects, and accessibility aspects. Strength (strength) is the existence of a variety of mangrove species, large land area, facilities, and accessibility that are easy to reach. Weaknesses, namely low marketing activities, some facilities that are not maintained, and aesthetic factors that are still lacking. The opportunities are strategic locations, creative community empowerment, and government support, while the threats are beach abrasion, land conversion, negative impacts of ecotourism activities, competition with other tourism objects, and logging of mangrove trees. The type of research used in this research is descriptive with qualitative techniques